INTEGRASI SAINS DAN AL-QUR’AN DALAM PEMBELAJARAN IPA DAN FISIKA - Nurul Zuriani; Cisita Azzahra; Elvi Silvi Yanti Pulungan; Luthfiyyah Maftah Syahruni; Muhammad Bisri Adinata (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The integration of science and the Quran is a learning approach that aims to eliminate the dichotomy between science and religious values ​​in education. To date, science and physics learning tends to emphasize cognitive and empirical aspects without linking them to spiritual values, resulting in students' understanding of science in a fragmented and less meaningful way. This research aims to examine the concept of science and Quran integration and analyze its implementation in science and physics learning. The method used in this research is a literature study with a descriptive qualitative approach, through the collection and analysis of various sources such as scientific journals, books, and relevant articles.The results show that the integration of science and the Quran can be achieved by linking scientific concepts to relevant Quranic verses, such as in the study of cosmology, physics, and biology.